Results of studying the fauna of Lepidoptera in the North Kazakhstan region (Republic of Kazakhstan) in 2019-2021 - Ivan A. Zuban; Svyatoslav A. Knyazev; Nadezhda V. Schevchuk; Yuliya N. Korobeinikova (Acta Biologica Sibirica, 2022)
The article presents the results of studying the fauna of Lepidoptera in the North Kazakhstan region in the field seasons of 2019-2021. The annotated list includes 219 species, including 37 species given for the first time for the North Kazakhstan region.